Games design and integration with user’s emotion - Ahmad, Ibrahim; Jaafar, Azizah (2011)
Design and development for computer game have been started more than four decades ago with first computer game production that named Spacewar. At that time, such game only used to throw single-handedly. However, nowadays, digital game competition can be shared individual leisure with routine activity. Computer game suitability influenced a lot by computer design itself. A study related to basic design to computer game development is getting less response. This is because it needs perusal on social aspect, emotion and association with human life. This working paper tries to suggest on User Centered Games Design that used in designing computer game such as Role Playing Games genre. At the same time, an early exploratory study related to computer game designs that wish to be produced will also be explained in this paper.